Cardiovascular Risk and Prediction Model of Vascular Endothelial Growth Factor Tyrosine Kinase Inhibitors in Patients with Liver Cancer - Yen-Chou Chen; Chun-Yao Huang; Li-Ming Lien; Jin-Hua Chen; Bagas Suryo Bintoro; Fang-I Hsieh (Cardiovascular Toxicology, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Mechanistic insights into temoporfin-based photodynamic therapy: Ferroptosis as a critical regulator under normoxic and hypoxic conditions in head and neck cancer - Tong-Hong Wang; Li-Fang Chou; Yen-Wen Shen; Nan-Chin Lin; Yin-Hwa Shih; Tzong-Ming Shieh (Journal of Photochemistry and Photobiology B: Biology, 2025)

Sexual dimorphism in zebrafish aggression and metabolism under acute ammonia stress - Fang Zhi Chua; Li-Yih Lin; Yung-Che Tseng; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Public opinion about solar radiation management: A cross-cultural study in 20 countries around the world - Nadja Contzen; Goda Perlaviciute; Linda Steg; Sophie Charlotte Reckels; Susana Alves; David Bidwell; Gisela Böhm; Marino Bonaiuto; Li-Fang Chou; Victor Corral-Verdugo; Federica Dessi; Thomas Dietz; et al. (Climatic Change, 2024)
Some argue that complementing climate change mitigation measures with solar radiation management (SRM) might prove a last resort to limit global warming to 1.5 °C. To make a socially responsible decision on whether to use SRM, it is important to consider also public opinion, across the globe and particularly in the Global South, which would face the greatest risks from both global warming and SRM. However, most research on public opinion about SRM stems from the Global North. We report findings from the first large-scale, cross-cultural study on the public opinion about SRM among the general public ( N = 2,248) and students ( N = 4,583) in 20 countries covering all inhabited continents, including five countries from the Global South and five ‘non-WEIRD’ (i.e. not Western, Educated, Industrialised, Rich, and Democratic) countries from the Global North. As public awareness of SRM is usually low, we provided participants with information on SRM, including key arguments in favour of and against SRM that appear in the scientific debate. On average, acceptability of SRM was significantly higher in the Global South than in the ‘non-WEIRD’ Global North, while acceptability in the ‘WEIRD’ Global North was in between. However, we found substantial variation within these clusters, especially in the ‘non-WEIRD’ Global North, suggesting that countries do not form homogenous clusters and should thus be considered individually. Moreover, the average participants’ views, while generally neither strong nor polarised, differed from some expert views in important ways, including that participants perceived SRM as only slightly effective in limiting global warming. Still, our data suggests overall a conditional, reluctant acceptance. That is, while on average, people think SRM would have mostly negative consequences, they may still be willing to tolerate it as a potential last resort to fight global warming, particularly if they think SRM has only minor negative (or even positive) impacts on humans and nature.

Combining hybrid nanoflowers with hybridization chain reaction for highly sensitive detection of SARS-CoV-2 nucleocapsid protein - Wen Yin; Ji Hu; Fang Chen; Li Zhu; Yingxin Ma; Nuo Wang; Hongping Wei; Hang Yang; Shan-Ho Chou; Jin He (Analytica Chimica Acta, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Localization and characterization of VVA0331, a 489-kDa RTX-like protein, in Vibrio vulnificus YJ016 - Li-Fang Chou; Hwei-Ling Peng; Yu-Chung Yang; Min-Chieh Kuo; Hwan-You Chang (Archives of Microbiology, 2009)

Evolution of Exceptionally Large Genes in Prokaryotes - Min-Chieh Kuo; Li-Fang Chou; Hwan-You Chang (Journal of Molecular Evolution, 2008)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Dynamic analysis of hepatoma spheroid formation: roles of E-cadherin and β1-integrin - Ruei-Zeng Lin; Li-Fang Chou; Chi-Chen Michael Chien; Hwan-You Chang (Cell and Tissue Research, 2006)